Commitment and Engagement of Educators: A Multi-Method Approach in the Philippine Cultural Context - Gamboa, Veronica R. (Future Science / FSH-PH Publications, 2025)
Due to the high attrition rates of teachers in private institutions in the Philippines, this multi-method quantitative study aims to investigate the extent of the influence of affective, normative, and continuance commitment to work engagement among professional teachers in private educational institutions. This includes qualitative insights into the cultural values and traits that affect them. A total of 184 samples were collected from professional Filipino teachers in six educational institutions. Multiple linear regression was employed, ensuring all assumptions were met. The results show that affective and normative commitment influence work engagement, while continuance does not. The teachers are primarily engaged and committed due to their interactions with students and colleagues, which are amplified through the Filipino cultural traits and values of kapwa (shared identity), pakikisama (social harmony), utang na loob (debt of appreciation), pakikipagkapwa (social identity), malasakit (care), and bahala na (acceptance of fate). This study explores work engagement and commitment among Filipino professional teachers in the Philippine cultural context, building on the theories of the job demands-resources model, social exchange, and norm reciprocity. Future studies can include novel well-being variables and intervention studies.